Analisis Pelanggaran Etika Profesi Akuntansi (Studi Kasus PT Bank Lippo Tbk) - Mochammad Irfan Saputra; Puput Widiyasari; Nova Fitrianti; Saridawati Saridawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze violations of accounting professional ethics that occur within PT Bank Lippo Tbk. Professional ethics in accounting is a crucial aspect in ensuring the reliability and integrity of a company's financial reports. The research findings indicate that there are several violations of accounting professional ethics that occur within PT Bank Lippo Tbk, including questionable accounting practices, manipulation of financial reports, and conflicts of interest between management and stakeholders. These violations have led to losses for shareholders, decreased public trust in the company, and threatened market stability. A thorough analysis of this case provides a better understanding of the importance of applying accounting professional ethics in daily corporate practices. The practical implications of this research include the need for strengthened internal and external oversight, increased awareness of ethics among accounting practitioners, and the implementation of stricter accounting standards to prevent future violations.